2015
DOI: 10.1002/brb3.360
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of the transcription of neuroplasticity‐related genes and variation in stress‐coping style

Abstract: IntroductionStress coping has been defined as the cognitive and behavioral efforts made to conquer, endure, or decrease external and internal demands and the conflicts between them. It has two main elements: the control or modification of the person–environment relationship causing the stress (i.e., problem-focused coping) and/or regulation of stressful feelings (i.e., emotion-focused coping). Research suggests that the expressions of brain-derived neurotrophic factor (BDNF) and neurotrophic tyrosine kinase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Another possible explanation may be differences in methods used to measure coping behaviors and the characteristics of the participants among studies (eg, age). For example, participants in this study were much older than those in a previous study showing a significant association between BDNF and emotion‐focused coping (average age: 55.0 vs 24.5 years, respectively) . Older participants exhibit reduced heritability of emotional regulation, possibly due to better skills for emotional regulation and advantageous characteristics (eg, more experience in coping with stress and higher social position).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Another possible explanation may be differences in methods used to measure coping behaviors and the characteristics of the participants among studies (eg, age). For example, participants in this study were much older than those in a previous study showing a significant association between BDNF and emotion‐focused coping (average age: 55.0 vs 24.5 years, respectively) . Older participants exhibit reduced heritability of emotional regulation, possibly due to better skills for emotional regulation and advantageous characteristics (eg, more experience in coping with stress and higher social position).…”
Section: Discussionmentioning
confidence: 55%
“…While candidate gene studies have examined genetic associations with coping behaviors, no such genome‐wide association study (GWAS) has been performed. Candidate gene studies have shown that polymorphisms in BDNF , NTRK2 , SLC64A and ADRB2 , which contribute to adaptation for psychosocial stress, are associated with some coping behaviors . As these candidate gene studies have only showed limited associations between coping behaviors and specific single nucleotide polymorphisms (SNPs), GWASs are needed to discover associations between unknown genes and coping behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Data revealed that the SNPs of the TrkB gene affected the mechanisms that are used to cope with stress in young Japanese people. It is worth stressing that individuals with the T/T genotype (polymorphic) of rs10868235 had lower scores for the cognitive strategies for relieving stress [19]. Cognitive impairment is common in schizophrenia patients, and stress is an important factor that modulates both the occurrence of and the course of schizophrenia [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate gene we examined in mice is SPRY2 , which encodes a protein that suppresses the actions of several neurotrophic factors (Kramer et al, 1999; Cabrita and Christofori, 2003; Rubin et al, 2003; Zhang et al, 2005; Gross et al, 2007) that may play role in coping with stress (Aizawa et al, 2015). Stress coping induced downregulation of SPRY2 observed in monkeys could therefore enhance neurotrophic actions and promote neural adaptations like those observed with decreased SPRY2 expression in rat models of electroconvulsive therapies for major depression (Ongur et al, 2007).…”
Section: Discussionmentioning
confidence: 99%